From memory regime to neoliberal violence: State of the art of third millennium fictions - Rivera Soto, José (Árboles y Rizomas, 2024)
In this article I propose that Chilean authors born in the eighties persist, as in the narratives of memory and postmemory, in the moral judgment of the dictatorship, but not only from the remembrance exercise but, above all, thematizing the multiple forms of neoliberal violence. To develop this generational reading proposal, I make a state of the art of a corpus made up of Daniela Catrileo, Paulina Flores, Cristóbal Gaete, Arelis Uribe and Diego Zúñiga. After analyzing the academic research around these authors, I conclude that, even when the traces of the military coup and the authoritarian period do not disappear, these narratives turn to neoliberalism in raw, realistic and intimate texts, assigning the violence of the model as inheritance of the Pinochet regime, being indivisible from its origin through state terrorism.